2021
DOI: 10.1038/s41551-021-00696-y
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle regeneration via the chemical induction and expansion of myogenic stem cells in situ or in vitro

Abstract: Muscle loss and impairment resulting from traumatic injury can be alleviated by therapies using muscle stem cells. However, harvesting sufficient numbers of autologous myogenic stem cells and expanding them efficiently has been challenging. Here, we show that myogenic stem cells (predominantly Pax7 + cells) selectively expanded from readily obtainable dermal fibroblasts or Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 63 publications
2
27
0
Order By: Relevance
“…It should be noted that skeletal muscle-resident stem cells (also known as muscle satellite cells) contribute to muscle regeneration in response to various injuries [40][41][42][43][44][45][46][47]. However, a previous study demonstrated that lifelong reduction of satellite cells neither accelerated nor exacerbated sarcopenia and that satellite cells did not contribute to the maintenance of muscle size or fiber type composition during aging, but that their loss may contribute to age-related muscle fibrosis [48].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that skeletal muscle-resident stem cells (also known as muscle satellite cells) contribute to muscle regeneration in response to various injuries [40][41][42][43][44][45][46][47]. However, a previous study demonstrated that lifelong reduction of satellite cells neither accelerated nor exacerbated sarcopenia and that satellite cells did not contribute to the maintenance of muscle size or fiber type composition during aging, but that their loss may contribute to age-related muscle fibrosis [48].…”
Section: Discussionmentioning
confidence: 99%
“…Plants and some animals can regenerate whole bodies such as Hydra (phylum Cnidaria) or flatworm (Platyhelminthes) that regenerate half or entire bodies when severed; plants can regenerate roots from severed stems (where roots did not exist before). When the environment of a leaf tissue segment is manipulated with phytohormones [ 9 , 13 , 14 ], or the environment of cultured mouse neonatal dermal fibroblasts is manipulated by chemicals [ 15 ], regeneration occurs to different degrees. Plants can regenerate whole shoots or roots, and animal cells can regenerate stem cells [ 15 ] or even entire animals [ 16 ].…”
Section: Types Of Regenerationmentioning
confidence: 99%
“…When the environment of a leaf tissue segment is manipulated with phytohormones [ 9 , 13 , 14 ], or the environment of cultured mouse neonatal dermal fibroblasts is manipulated by chemicals [ 15 ], regeneration occurs to different degrees. Plants can regenerate whole shoots or roots, and animal cells can regenerate stem cells [ 15 ] or even entire animals [ 16 ]. Plant cells’ plasticity is revealed in the ability to form shoots or roots from somatic cells and the capacity to generate entier embryos without fertilization, a process is known as somatic embryogenesis, not to confuse with parthenogenesis with is the formation of an embryo in an unfertilized egg cell.…”
Section: Types Of Regenerationmentioning
confidence: 99%
“…Plants and some animals can regenerate whole bodies like Hydra (phylum Cnidaria) or flatworm (Platyhelminthes) that regenerate half or entire bodies when severed; plants can regenerate roots from severed stems (where roots did not exist before). When the environment of a leaf tissue segment is manipulated with phytohormones [9,13,14], or the environment of cultured mouse neonatal dermal fibroblasts is manipulated by chemicals [15], regeneration occurs to different degrees. Plants can regenerate whole shoots or roots, and animal cells can regenerate stem cells [15] or even entire animals [16].…”
Section: Types Of Regenerationmentioning
confidence: 99%